2015
DOI: 10.1002/art.39261
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Enrichment of Activated Group 3 Innate Lymphoid Cells in Psoriatic Arthritis Synovial Fluid

Abstract: Objective Innate lymphoid cells (ILCs) are a recently discovered group of cells that are essential to epithelial homeostasis and are implicated in psoriasis pathogenesis, yet they have never been reported in psoriatic arthritis (PsA). Methods ILC classes and subsets were characterized in the peripheral blood (PB) of healthy controls, patients with psoriasis, and patients with PsA and in the synovial fluid (SF) of patients with PsA and patients with rheumatoid arthritis (RA). Cell surface marker expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 17 publications
(23 reference statements)
6
61
0
1
Order By: Relevance
“…We have demonstrated that ILC subset frequency and transcriptional profile are altered in SFMCs isolated from JIA patients, and that among the ILC subsets identified within JIA SFMCs, an expansion of NCR− ILC3s has the strongest association with multiple measures of clinical severity. NCR− ILC3s can be characterized by the expression of the transcripts for RORC2 and IL‐17A, similar to Th17 cells, and they can be found expanded in IL‐17A–driven pathologies . Taken together, these data suggest that the IL‐17A+CD4+ T cell signature we have previously described in JIA SF may extend to other cell types including ILCs .…”
Section: Resultssupporting
confidence: 67%
“…We have demonstrated that ILC subset frequency and transcriptional profile are altered in SFMCs isolated from JIA patients, and that among the ILC subsets identified within JIA SFMCs, an expansion of NCR− ILC3s has the strongest association with multiple measures of clinical severity. NCR− ILC3s can be characterized by the expression of the transcripts for RORC2 and IL‐17A, similar to Th17 cells, and they can be found expanded in IL‐17A–driven pathologies . Taken together, these data suggest that the IL‐17A+CD4+ T cell signature we have previously described in JIA SF may extend to other cell types including ILCs .…”
Section: Resultssupporting
confidence: 67%
“…Another crucial factor is the analysis of tissues that are not relevant to the disease. Reports from recent translational rheumatology studies described IL‐17–producing ILCs in the gut of patients with AS‐associated IBD , in the SF of patients with psoriatic arthritis (PsA) , in the skin of patients with psoriasis (), and in normal enthesis samples obtained from donors without systemic inflammatory disease , but not in the inflamed synovium, enthesis, or spine, the key target tissues in SpA.…”
Section: Discussionmentioning
confidence: 99%
“…ILC3s play an important role in the regulation of tissue homeostasis, repair, and inflammation (20) and, similar to their Th17 cell counterparts, have been proposed to produce IL-17A, IL-22, and GM-CSF (16). Recent studies have suggested that IL-17-producing ILC3s are amplified in the inflamed tissue of patients with SpA (23)(24)(25). However, whether ILC3s constitute an important source of IL-17A in SpA synovitis remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Это свиде-тельствует об определенных различиях патогенетических механизмов СпА у женщин и у мужчин и позволяет объ-яснить природу более тяжелого поражения осевого скеле-та у последних, несмотря на сходную выраженность боли и функциональных нарушений [53]. Следует обратить внимание на то, что при СпА не только Th17-клетки, но и клетки врожденной иммунной системы активно син-тезируют ИЛ17, особенно в пораженных тканях [54][55][56][57]. В частности, было показано, что ILC3-клетки при стиму-ляции ИЛ23 синтезируют избыточное количество ИЛ17, ИЛ22 и других «провоспалительных» цитокинов [57].…”
Section: таблицаunclassified